190k views
5 votes
Question 3 (1 point)
.
2x - 3(x + 6) = -3(x - 2)
x =

User Zabbala
by
6.0k points

2 Answers

2 votes

Answer:


x = 12

Explanation:


2x - 3(x + 6) = - 3(x - 2) \\ 2x - 3x - 18 = - 3x + 6 \\ 2x - 3x + 3x = 18 + 6 \\ 2x = 24 \\ \\ x = (24)/(2) \\ \\ x = 12

User Shorol
by
5.6k points
2 votes

Answer:

x=12

Explanation:

2x - 3(x + 6) = -3(x - 2)

Distribute

2x -3x -18 = -3x +6

Combine like terms

-x -18 = -3x+6

Add 3x from each side

-x+3x -18 = -3x+3x +6

2x -18 = 6

Add 18 to each side

2x-18+18 = 6+18

2x = 24

Divide each side by 2

2x/2 = 24/2

x = 12

User Alberto Vielma
by
5.7k points